The effect of reduced graphene oxide on the catalytic activity of Cu–Cr–O–TiO2 to enhance the thermal decomposition rate of ammonium perchlorate: an efficient fuel oxidizer for solid rocket motors and missiles. Issue 58 (24th July 2017) - Kumar, Harish; Tengli, Prahalad N.; Mishra, Vijay Kumar; Tripathi, Pankaj; Bhushan, Awani; Mishra, Pradeep Kumar
Abstract : Schematic image of rocket having solid composite propellant modified with prepared catalyst. Abstract : Reduced graphene oxide (rGO) modified transition metal oxide based composites were successfully synthesized via a sol–gel assisted Hummers' method. The present study includes the synthesis of CuCr2 O4 ·0.7TiO2, the synthesis of rGO and the synthesis of rGO modified CuCr2 O4 ·0.7TiO2 . In order to synthesize the desired catalyst, rGO and Cu–Cr–O–0.7TiO2 were synthesized individually. The CuCr2 O4 ·0.7TiO2 composite was synthesized via a sol–gel method. Reduced graphene oxide (rGO) used as a modifier in the catalyst, was also synthesized in the laboratory and was calcined at high temperature (1050 °C) to improve its activity. Finally, Cu–Cr–O–0.7TiO2 was modified with 10 wt% rGO. The post synthesis characterizations were performed using various instrumental techniques including X-ray diffraction (XRD) for phase analysis, Fourier transform infrared (FTIR) and Raman spectroscopy for molecular interactions, scanning electron microscopy (SEM) for surface morphology, energy dispersive X-ray analysis (EDX), elemental analysis and X-ray photoelectron spectroscopy (XPS) for binding energy. The catalytic efficiency of the synthesized composite catalyst samples based thermal decomposition of the host material ( i.e. AP) was determined by differential thermal analysis (DTA) and thermogravimetric analysis (TGA). The rGO modification into the Cu–Cr–O–0.7TiO2 tri-metallic composition made it the most promising catalyst for the thermal decomposition of AP, due to the tremendously high electrical and thermal conductivity of rGO. Different amounts (2.5, 5.0, 7.5 and 10 wt%) of Cu–Cr–O–0.7TiO2 –rGO were added to ammonium perchlorate (AP) to investigate its effect on the thermal decomposition of AP, which is a well known oxidizer used worldwide in the solid composite propellant (SCP) in modern rocketry. The 5 wt% of catalyst (Cu–Cr–O–0.7TiO2 –rGO) addition into AP exhibited the remarkably enhanced thermal decomposition of AP. Finally, the burn rate of SCP was examined with 5 wt% catalyst modified AP. The 5 wt% of catalyst modified AP exhibited 175.31% higher burn rate of SCP, compared to the burn rate of pure AP added SCP. Furthermore, when it was compared with an industrial catalyst, i.e. activated copper chromite (ACR), it showed 133.61% higher burn rate of SCP. The SCP exhibited excellent ballistic performance with 0.6% of catalyst in AP, which enhanced the burn rate from 4.866 mm s −1 (for SCP having pure AP) to 8.531 mm s −1 (for SCP having catalyst added AP) and 6.385 mm s −1 (for SCP having industrial catalyst added AP) at 33 bar.